#### Answer

The equation in the example is symmetric with respect to the $y$-axis.

#### Work Step by Step

To verify that the equation is symmetric with respect of the $y$ -axis, substitute $x=-x$ in the above equation. If after putting $x=-x$, the resultant equation is the same as the given equation, then the equation is symmetric with respect to the $y$-axis.
$\begin{align}
& y={{x}^{2}}-2 \\
& y={{\left( -x \right)}^{2}}-2\text{ } \\
& y={{x}^{2}}-2
\end{align}$
Since the resultant equation is the same as the given equation, the equation is symmetric with respect to the $y$-axis.